Strength of Social Environmental Support and Off-Farm Accessibility as Determinants of Young Farmers' Willingness to Persist in Agriculture - Fitrianti, Wanti; Sudrajat, Jajat; Suyatno, Adi (Universitas Galuh, 2025)
The poor regeneration of farmers is a significant strain on the Indonesian agricultural sector. The negative stereotypical view of the farming profession is the cause of the reluctance of the younger generation to get involved and persist in agriculture. However, there is a strong potential for environmental support and land access as well as access to off-farm work to be factors that can encourage young farmers to remain in agriculture. The purpose of this study is to analyze the determinants of the willingness of young farmers to continue in the agricultural sector, specifically on the outskirts of Pontianak, West Kalimantan. This is accomplished by taking into account the proximity of the area to the city center, as well as certain demographic factors, in which the choice of occupation and decision to remain a farmer presents numerous obstacles. This study took a quantitative approach, with a sample size of 47 persons, and was analyzed using logistic regression. The findings of the study indicate that social environmental support from family and residents has a significant impact on young farmers' willingness to continue in agriculture. Social environmental support will help to eradicate negative stereotypes about farming, increasing young farmers' trust and confidence that becoming a farmer will give them pride and a secure future. The results of this study also demonstrate that growing levels of education, farming experience, and off-farm job access improve the likelihood of young farmers' willingness to continue in the agricultural sector.